2015
DOI: 10.1109/joe.2014.2317955
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach to Analysis of Phytoplankton Images

Abstract: Abstract-The main objective of this paper is detection, recognition, and abundance estimation of objects representing the Prorocentrum minimum (Pavillard) Schiller (P. minimum) species in phytoplankton images. The species is known to cause harmful blooms in many estuarine and coastal environments. The proposed technique for solving the task exploits images of two types, namely, obtained using light and fluorescence microscopy. Various image preprocessing techniques are applied to extract a variety of features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Examples include the work of Gorsky et al (1989) wherein they were able to distinguish species of phytoplankton with distinct size and shape using simple geometric properties. Culverhouse et al (2003) employed neural network technique utilizing different texture and edge-based image properties in classifying dinoflagellate images and Verikas et al (2014) used support vector machine (SVM) and random forest (RF) classifiers to discriminate the HAB-causing Prorocentrum minimum. The work of Sosik and Olson (2007b) may be the most detailed multiclass categorization of phytoplankton images from Imaging FlowCytobot.…”
Section: Optimization Of Flowcam's Auto-classification Capabilitymentioning
confidence: 99%
“…Examples include the work of Gorsky et al (1989) wherein they were able to distinguish species of phytoplankton with distinct size and shape using simple geometric properties. Culverhouse et al (2003) employed neural network technique utilizing different texture and edge-based image properties in classifying dinoflagellate images and Verikas et al (2014) used support vector machine (SVM) and random forest (RF) classifiers to discriminate the HAB-causing Prorocentrum minimum. The work of Sosik and Olson (2007b) may be the most detailed multiclass categorization of phytoplankton images from Imaging FlowCytobot.…”
Section: Optimization Of Flowcam's Auto-classification Capabilitymentioning
confidence: 99%
“…In Verikas et al (2015), a unary-class classification system is proposed to detect multiple phytoplankton in an image. In this work, image segmentation, 100 global and local shape features, feature selection, SVM and RF classifiers are applied.…”
Section: Original Methodsmentioning
confidence: 99%
“…Santhi et al [ 28 ] identified algal from microscopic images by applying ANN on extracted and reduced features such as texture, shape, and object boundary. Verikas et al [ 29 ] exploited light and fluorescence microscopic images to extract geometry, shape and texture feature sets which were then selected and used in SVM as well as RF classifiers to distinguish between Prorocentrum minimum cells and other objects.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the aforementioned methods shows the performance of plankton image classification systems based on applied features and classifiers, among which the general features, such as size, invariant moments, co-occurrence matrix, Fourier descriptor, etc., and the traditional classifiers, such as SVM, RF, ANN, etc., are most commonly used respectively [ 8 , 11 13 , 17 , 20 , 25 , 27 , 29 ]. However, these features usually suffer from robustness shortage and cannot represent the biomorphic characteristics of plankton well.…”
Section: Introductionmentioning
confidence: 99%